2022
DOI: 10.1002/masy.202100294
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of UHMWPE (Disc) against Ti6Al4V (Pin) under Different Lubrication Conditions

Abstract: The proposed research work is addressed to the study of the wear behavior of Ultra High Molecular Weight Polyethylene (UHMWPE) under the contact with a rounded pin in Ti6Al4V alloy, which is largely used for production of the last generation of prosthetic implants by electron beam manufacturing (EBM). The wear tests of UHMWPE in contact with a Ti6Al4V pin are carried out dry or in the presence of lubricants fluids that are characterized by tribological tests, wet-ability measurements, and morphological observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In engineering applications, the quantity K/H = V/(P•L) (mm 3 /(N•m), defined as specific wear rate, is often more useful in cases where hardness H is difficult to evaluate [10]. To avoid errors in evaluation, both the wear coefficient and the specific wear rate must be referred to the stationary quantities and therefore the ratio V/L represents the slope of this stage, i.e., the derivative (dV/dL)s. The data in Table 4 show the specific wear rates for the contact Ti6Al4V alloy tip-UHMWPE sheet in the three different lubrication conditions, calculated as a ratio between the slope in the stationary stage (dV/dL)s and the applied load (P), differently from what was done in [8,9]. As pointed out in [9], in dry conditions the wear track on the polymer sheet is deeper and particularly accentuated in the center.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In engineering applications, the quantity K/H = V/(P•L) (mm 3 /(N•m), defined as specific wear rate, is often more useful in cases where hardness H is difficult to evaluate [10]. To avoid errors in evaluation, both the wear coefficient and the specific wear rate must be referred to the stationary quantities and therefore the ratio V/L represents the slope of this stage, i.e., the derivative (dV/dL)s. The data in Table 4 show the specific wear rates for the contact Ti6Al4V alloy tip-UHMWPE sheet in the three different lubrication conditions, calculated as a ratio between the slope in the stationary stage (dV/dL)s and the applied load (P), differently from what was done in [8,9]. As pointed out in [9], in dry conditions the wear track on the polymer sheet is deeper and particularly accentuated in the center.…”
Section: Discussionmentioning
confidence: 97%
“…However, wearing contact with metal parts can lead to the release of debris, limiting the use of UHMWPE. Therefore, several experimental researches have been addressed to studying the improving effects on wear behavior due to lubrication [8] or to the development of suitable polymer composites [9]. In these works, the metal-polymer contact was reproduced by means of a "pin on disc" apparatus, in which a Ti6Al4V alloy pin, produced by EBM, acts through the pointed end on a polymer sheet, which is placed on a rotating disc.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the mechanical and wear resistance of UHMWPE, researchers have undertaken various strategies. These include co-blending modification, chemical alteration, incorporating fillers, and radiation cross-linking. For instance, Wu, Tai, and colleagues explored UHMWPE composites modified through irradiation cross-linking and graphene oxide. Their investigations revealed that these modifications effectively enhanced the physicochemical, mechanical, and tribological properties of the composites, making them more resilient to oxidative degradation. Additionally, Oral demonstrated that high-temperature melting followed by radiation cross-linking could further boost the toughness of UHMWPE due to a lower cross-link density .…”
Section: Introductionmentioning
confidence: 99%